ANALISIS PERKEMBANGAN WILAYAH KECAMATAN KARTASURA SEBAGAI KAWASAN STRATEGIS CEPAT TUMBUH - A Anisah; S Soedwiwahjono; Nur Miladan (TATALOKA, 2018)
Regional development components are growth center and hierarchy of region. Indonesia begin to promote the goal of equitable development and the economy embodied with regional development concepts, which is one of them is the concept of rapidly growing strategic area. This concept sees the area as an internal and central area which is affecting the surrounding area. Therefore, it is necessary to analyze the regional development of KSCT in order to know how developed internal area and the impact which is distinguished by two approaches that are economic growth and spatial. This research uses the longitudinal development method with the analytical approach used is deductive and quantitative descriptive research type. The compilation and analysis techniques used are primary data (observation, interview) and secondary data collection; Descriptive, descriptive statistics, GIS and overlay, Scalogram and Marshall Index, Gravity Model and Breaking Point, ICOR, LQ, and Klassen Typology. There are two outcomes: Kartasura District as itself and its impact to the surrounding area. In its internal area, the development of the area that occurred in 2011 has not been able to change much from economic growth and spatial development, and there is an internal gap which becomes obstacle for its development as the rapidly growth strategic area. While the impact on Sukoharjo District has begun to be seen with the contribution of local revenue that has been able to independently, however, the existing base sector has not been evenly distributed in all sectors and not all have been developed quickly. For the surrounding area, it had already an impact as a center of the rapidly growth strategic area.